Customized yeast cell factories for biopharmaceuticals: from cell engineering to process scale up - Madhavan, Aravind (Microb Cell Fact, 2021)
The manufacture of recombinant therapeutics is a fastest-developing section of therapeutic pharmaceuticals and presently plays a significant role in disease management. Yeasts are established eukaryotic host for heterologous protein production and offer distinctive benefits in synthesising pharmaceutical recombinants. Yeasts are proficient of vigorous growth on inexpensive media, easy for gene manipulations, and are capable of adding post translational changes of eukaryotes. Saccharomyces cerevisiae is model yeast that has been applied as a main host for the manufacture of pharmaceuticals and is the major tool box for genetic studies; nevertheless, numerous other yeasts comprising Pichia pastoris, Kluyveromyces lactis, Hansenula polymorpha, and Yarrowia lipolytica have attained huge attention as non-conventional partners intended for the industrial manufacture of heterologous proteins. Here we review the advances in yeast gene manipulation tools and techniques for heterologous pharmaceutical protein synthesis. Application of secretory pathway engineering, glycosylation engineering strategies and fermentation scale-up strategies in customizing yeast cells for the synthesis of therapeutic proteins has been meticulously described.